European Questionnaire for Job Analysis (EQJA) - Biela , Adam; Rożnowski, Bohdan (Studia Oeconomica Posnaniensia, 2018)
The paper presents a tool for Job analysis called: European Questionnaire for Job Analysis (EQJA). It is one of the general methods for job analysis which should be used by experts. This tool is recommended to achieve many aims connected with job analysis: ergonomics, accident prevention, job designing, recruitment and selection, employees' development etc.